Comparative Analysis of Traditional and Modern Fermentation for Xuecai and Correlations Between Volatile Flavor Compounds and Bacterial Community - Zhang, Jianming; Zhang, Chengcheng; Xin, Xiaoting; Liu, Daqun; Zhang, Wenwu (Frontiers in Microbiology, 2021)
Differences in flavor compounds and bacterial communities of Xuecai by traditional and modern fermentation are poorly understood. Allyl isothiocyanate (E9), ethyl acetate (E1), 3-butenenitrile (N1), phenol (P1), ethanol (A1) and 3-(2,6,6-trimethyl-1-cyclohexen-1-yl) acrylaldehyde (L11) were the main flavor compounds that differed between Xuecai produced by traditional and modern fermentation. Among these compounds, the contents of N1 and E9 were higher in modern fermentation Xuecai. Traditional fermentation Xuecai possessed higher contents of A1, P1, E1 and L11. High-throughput sequencing showed that Lactobacillus was the most abundant genus (50%) in modern fermentation Xuecai. However, in traditional fermentation Xuecai, Halanaerobium (29.06%) and Halomonas (12.96%) were the dominant genera. Halophilic bacteria positively contribute to the flavor of Xuecai. Carbohydrate metabolism and amino acid metabolism were the most abundant pathways associated with the bacterial communities of the Xuecai. This indicated that Xuecai flavor formation is mainly dependent on protein and carbohydrate degradation. This study provides a novel insight that halophilic bacteria may be important for flavor formation of Xuecai.